The Relationship Between the Implementation of Health Protocols Before and After Covid-19 Vaccination in Students of The Faculty of Medicine, YARSI University Class of 2019 and the review in Islam - Auliya Sabilla Rosyada; Rika Ferlianti; Siti Maulidya Sari; Muhammad Arsyad (Junior Medical Journal, 2022)
Background: Severe Acute Respiratory Syndrome Coronavirus 2(SARS-COV-2) is the cause of Corona Virus Disease-19 (Covid-19) which was designated by the World Health Organisation WHO as a pandemic. In Islam, the occurrence of a plague has occurred in the time of the Prophet Muhammad SAW by being ordered to avoid its spread. The spread of Covid-19 can be minimized by carrying out health protocols including vaccinations. Vaccination has benefits to reduce the risk of contracting Covid-19 so that it can form perceptions in the community and begin to not comply with health protocols. This research was conducted on students of the Faculty of Medicine, YARSI University class of 2019 with the aim of assessing whether there is a relationship between vaccination and changes in health protocol discipline.Method: Type of research in the form of an analytical survey with a cross-sectional research design. Questionnaires are distributed with google forms. This research was conducted on students of the Faculty of Medicine, YARSI University class of 2019 as many as 171 respondents. The analysis carried out is univariate and bivariate using pearson correlation.Results: Based on the results of statistical tests, there is a relationship between vaccination and changes in health protocols in respondents. In this study, it was found that respondents were more obedient after vaccination.Conclusion: There is a relationship between vaccination and changes in health protocol compliance.